5(p-3)=-2(7-2p)-5

Simple and best practice solution for 5(p-3)=-2(7-2p)-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(p-3)=-2(7-2p)-5 equation:



5(p-3)=-2(7-2p)-5
We move all terms to the left:
5(p-3)-(-2(7-2p)-5)=0
We add all the numbers together, and all the variables
5(p-3)-(-2(-2p+7)-5)=0
We multiply parentheses
5p-(-2(-2p+7)-5)-15=0
We calculate terms in parentheses: -(-2(-2p+7)-5), so:
-2(-2p+7)-5
We multiply parentheses
4p-14-5
We add all the numbers together, and all the variables
4p-19
Back to the equation:
-(4p-19)
We get rid of parentheses
5p-4p+19-15=0
We add all the numbers together, and all the variables
p+4=0
We move all terms containing p to the left, all other terms to the right
p=-4

See similar equations:

| 5=4g-19 | | (-8/9)y=-16/7 | | -8y+4(y+2)=18 | | 4(u+8)-8u=-8 | | 3p2−10p=14 | | V2-v=72 | | -8/9y=-16/7 | | 2w-3=+5 | | 3x−4=113x−4=11 | | -2n+6(-2n+8)=132 | | 0=5x^2-5x+2 | | 13x+60-44x-3=274 | | x/12=3/15 | | 12-b/7=13 | | d=(15)(6)+1/2(9.8)(6^2) | | 0=16t^2+1500 | | X-12y=-1 | | 36+r=5r+6(-4+r) | | 5x+14+7x=104 | | -7=9+c/6 | | x+91+160+80+100=900 | | 5(y-2)-2=2 | | 17+m/3=-1 | | 9•x=100 | | 50=15+10x | | -2b+6=-2b-2b | | 50+25x=55+22x | | -.66x+0.36x=7.2 | | 98+n/3=65 | | 25x^{2}+10=46 | | 11r=-44 | | 3x+2=+29 |

Equations solver categories